Highly-efficient optical sampling based on two-photon absorption in a semiconductor micro-cavity device - Donegan, John; Bradley, Louise (My University, 2005)
We demonstrate a highly-efficient optical sampling system based upon the nonlinear process of two-photon absorption in a specially designed semiconductor microcavity. The sensitivity of the system is around 0.1 mW/sup 2/ and the temporal resolution is 2 ps.
Proceedings of SPIE, Opto-Ireland 2005: Optoelectronics, Photonic Devices, and Optical Networks
SPIE Opto-Ireland 2005
PUBLISHED
Dublin
Keywords: Physics